2019
DOI: 10.7554/elife.50663
|View full text |Cite
|
Sign up to set email alerts
|

Lactate-mediated epigenetic reprogramming regulates formation of human pancreatic cancer-associated fibroblasts

Abstract: Even though pancreatic ductal adenocarcinoma (PDAC) is associated with fibrotic stroma, the molecular pathways regulating the formation of cancer associated fibroblasts (CAFs) are not well elucidated. An epigenomic analysis of patient-derived and de-novo generated CAFs demonstrated widespread loss of cytosine methylation that was associated with overexpression of various inflammatory transcripts including CXCR4. Co-culture of neoplastic cells with CAFs led to increased invasiveness that was abrogated by inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 66 publications
1
104
0
Order By: Relevance
“…For example, Damiani et al have observed that TCA intermediates that are not used for biomass purposes can be disposed via lactate production (34). Hence, while lactate is a metabolic intermediate, it has numerous downstream effects as known to occur via cell redox changes (14), allosteric binding (47), metabolic reprograming (26), and lactylation (25). The downstream effects of lactate in cancer remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Damiani et al have observed that TCA intermediates that are not used for biomass purposes can be disposed via lactate production (34). Hence, while lactate is a metabolic intermediate, it has numerous downstream effects as known to occur via cell redox changes (14), allosteric binding (47), metabolic reprograming (26), and lactylation (25). The downstream effects of lactate in cancer remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that lysine lactylation (Kla) levels increased in a dose-dependent fashion in response to exogenous L-lactate and that endogenous production of lactate is a key determinant of histone Kla levels (25). Furthermore, Verma's group has recently and elegantly demonstrated that tumor-mediated lactate can elicit epigenomic reprograming of cancer-associated fibroblasts from pancreatic ductal adenocarcinoma (26).…”
Section: Introductionmentioning
confidence: 99%
“…The fourth study described is an epigenomic analysis of patient-derived and de novo generated PDA CAFs performed by Bhagat et al, who demonstrated that a widespread loss of DNA methylation was associated with the overexpression of various inflammatory genes, including interleukins and chemokines, such as IL1A, CCL5, and CCL26 , and cellular receptors, such as CXCR4 and ICAM3 , which are all involved in critical cell signaling pathways in tumor progression. 94 Interestingly, metabolite tracing used in this study revealed that the lactate produced by PDA tumor cells led to increased MSC production of alpha-ketoglutarate (aKG), an important cofactor of the DNA demethylase TET. Conversely, aKG mediated the activation of TET enzymes, which led to decreased DNA methylation during the de novo differentiation of MSCs to CAFs.…”
Section: Epigenetic Regulation Of Stromal and Immune Cells Within Thementioning
confidence: 83%
“…During the last decade, studies on the epigenetic interplay between immune, stromal and cancer cells in the tumor microenvironment have emerged. These publications were particularly focused on the impact of epigenetics on the formation of CAFs (cancer associated fibroblasts) and CD8 T cell exhaustion (TOX) but more data on CD4 T cell biology need to be collected [57][58][59].…”
Section: Epigenetic Factors Leading To Th17 Cell Predominance In Thementioning
confidence: 99%